Behaviour change interventions in breast and cervical cancer screening promotion - Savicka, Vita; Circene, Ingrida (Information & Media, 2020)
To encourage women to participate in breast and cervical state-paid screening programs, an experiment was conducted, during which easy access was provided to the screening and each woman who had not used the state-paid screening opportunity was addressed through direct communication. Screening coverage after the experiment improved up to 288%, demonstrating the importance of a behavioural economics nudge approach and tailored communication in the overall health communication process provided within the socio-ecological model.